2022
DOI: 10.1111/1759-7714.14431
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive impact of neutrophil‐to‐lymphocyte ratio and HLA‐I genotyping in advanced esophageal squamous cell carcinoma patients receiving immune checkpoint inhibitor monotherapy

Abstract: Background: Immune checkpoint inhibitors (ICIs) have become standard-of-care in patients with pretreated advanced esophageal squamous cell carcinoma (ESCC). However, reliable biomarkers for clinical outcomes are lacking for ICIs. The exploration of effective biomarkers is therefore needed to optimize patient benefit in the treatment of ESCC. Methods: Sixty-nine patients with advanced ESCC enrolled at one center from two prospective trials were consecutively analyzed. NLR was dynamically collected and high-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In total, 38 studies involving 4154 patients were included in this meta-analysis and systematic review [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Thirty-seven studies had a retrospective study design, and only one study was prospective [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 38 studies involving 4154 patients were included in this meta-analysis and systematic review [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Thirty-seven studies had a retrospective study design, and only one study was prospective [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of patients with increased NLR ranged from 24.6% to 60.8% in 12 studies, and the pooled percentage of patients with increased NLR was 49.7% (95CI%: 43.7–55.8%) ( Figure S1 ). Although ICI treatment did not influence the trend in NLR overall, six studies [ 27 , 32 , 37 , 42 , 45 , 53 ] reported that the NLR level in patients without response to immunotherapy tended to significantly increase after ICI treatment, and in contrast, patients who responded to ICI treatment have similar or lower NLR level before and after immunotherapy ( Table S1 ). Notably, a retrospective study with data from a multicenter prospective trial using a mixed effects regression analysis with per-patient random intercept reported that patients with CR/PR/SD had a lower log-transformed NLR at study entry ( p = 0.03) and the NLR level was stable during follow-up overall [ 37 ], which corresponded to our results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations